Preventative Care Objective Structured Clinical Examination (OSCE) Based on USPSTF Guidelines December 2011 - Deanna R. Willis; Scott Renshaw; Shoba Pais; Jennifer Custer; Erin E. Krebs; Richard Kiovsky (Association of American Medical Colleges, 2012)
Abstract This objective structured clinical exam (OSCE) was developed to assess learner knowledge in preventative care, as well as learner ability to find and interpret evidence-based guidelines for preventative care of adult patients. It is a new approach to assessing evidence-based preventative care recommendations. Four different standardized patient cases, which can be used to evaluate student performance across gender, age, socioeconomic status, and race/ethnicity, are available. The OSCE was piloted with more than 150 students and showed good differentiation in scores, with score differentiation found to have clinical validity by practicing physicians. Practicing clinical experts took the OSCE to validate it as well, scoring more than one standard deviation above student completers. Pilot data showed that high scorers had more appropriate test orders and low scorers hade more inappropriate test orders. If more than one case is implemented, the OSCE has the ability to evaluate scores across patient socioeconomic status and race/ethnicity. In addition, this OSCE can be graded electronically or by nonclinical staff via use of the scoring sheet. The scoring sheet will need to be updated to current U.S. Preventive Services Task Force guidelines at the time of use.